Implementation of P5 in the Merdeka Curriculum towards Strengthening the Character of Love for the Motherland in Early Childhood - Ni Made Ayu Sekar Krisnawati; Desak Putu Parmiti (Universitas Pendidikan Ganesha, 2023)
National education in Indonesia implements various aspects of development by increasing abilities and forming dignified character in students. This research aims to analyze the implementation of P5 in the independence curriculum on the character of patriotism. This type of research is research that uses qualitative descriptive research methods. This research focuses on implementing P5 and strengthening the character of patriotism in early childhood. The population of this research is students and children's teachers. This research also uses observation, interview, and documentation data collection methods to collect data from group teacher subjects and principal informants. Data validity uses data analysis techniques such as triangulation, which consists of data reduction, data presentation, and drawing conclusions or verification. The results of this research show that implementing P5 as an effort to increase the character of patriotism is carried out in three stages. In the initial stage, the teacher deepens the child's talent interests to adjust the activities and themes of the P5 project. Project activities will be developed and arranged at the development stage based on a predetermined project theme. At the conclusion stage, the teacher will evaluate and reflect on the activities that have been carried out based on the children's achievements and feedback from parents. Apart from that, in its implementation, the six dimensions of the Pancasila Student Profile are also inserted into children's learning and daily life to familiarize children with character development.